Güncel Bakış Açısıyla Psikolojiye Giriş - Yazıcı, Zeynep; Çimen, Fatmanur; Aktu, Yahya; Epli, Hatice; Çolak Turan, Tuğba Seda; Ulaş, Sümeyye; Turgut, Özden; Ay, İsmail and Alkım Arı, Fikriye and Fırat, Sunay and Erk, Mehmet Aykut and Tatlı, Eda and Mert, Abdullah and Akdeniz, Seher (Academician Publishing Book DOI Portal, 2023)
-